Cross-over endocytosis of claudins is mediated by interactions via their extracellular loops - Gehne, Nora; Lamik, Agathe; Lehmann, Martin; Haseloff, Reiner F.; Andjelkovic, Anuska V.; Blasig, Ingolf E. (PLOS ONE, 2017)
Claudins (Cldns) are transmembrane tight junction (TJ) proteins that paracellularly seal endo- and epithelial barriers by their interactions within the TJs. However, the mechanisms allowing TJ remodeling while maintaining barrier integrity are largely unknown. Cldns and occludin are heterophilically and homophilically cross-over endocytosed into neighboring cells in large, double membrane vesicles. Super-resolution microscopy confirmed the presence of Cldns in these vesicles and revealed a distinct separation of Cldns derived from opposing cells within cross-over endocytosed vesicles. Colocalization of cross-over endocytosed Cldn with the autophagosome markers as well as inhibition of autophagosome biogenesis verified involvement of the autophagosomal pathway. Accordingly, cross-over endocytosed Cldns underwent lysosomal degradation as indicated by lysosome markers. Cross-over endocytosis of Cldn5 depended on clathrin and caveolin pathways but not on dynamin. Cross-over endocytosis also depended on Cldn-Cldn-interactions. Amino acid substitutions in the second extracellular loop of Cldn5 (F147A, Q156E) caused impaired cis- and trans-interaction, as well as diminished cross-over endocytosis. Moreover, F147A exhibited an increased mobility in the membrane, while Q156E was not as mobile but enhanced the paracellular permeability. In conclusion, the endocytosis of TJ proteins depends on their ability to interact strongly with each other in cis and trans, and the mobility of Cldns in the membrane is not necessarily an indicator of barrier permeability. TJ-remodeling via cross-over endocytosis represents a general mechanism for the degradation of transmembrane proteins in cell-cell contacts and directly links junctional membrane turnover to autophagy.